Mechanism of perfluorooctanesulfonate (PFOS)-induced apoptosis in the immunocyte. (March 2013) - Zhang, Ying-Hua; Wang, Jing; Dong, Guang-Hui; Liu, Miao-Miao; Wang, Da; Zheng, Li; Jin, Yi-He
<x xml:space="preserve">Abstract</x> As a new type of persistent organic pollutant, perfluorooctane sulfonate (PFOS) has raised great concern in recent years due to its ubiquitous distribution in the general environment and its long elimination half-life in humans. PFOS has toxic and carcinogenic effects in animals and humans, but the effects of PFOS on apoptosis are still not clear. The present study aimed to determine the mode of cell death and its mechanism in splenocytes and thymocytes from adult male C57BL/6 mice administered 0, 1, 5, or 10 mg PFOS/kg/day by gavage daily for 7 days. The results showed that more apoptotic cells were present in PFOS-treated mice than in control mice. PFOS induced production of reactive oxygen species (ROS), dissipation of mitochondria membrane potential, and apoptosis of splenocytes and thymocytes. Moreover, activities of superoxide dismutase, catalase, and glutathione reductase were increased, whereas activities of glutathione-S-transferase and glutathione peroxidase were decreased, in splenocytes. Glutathione contents were reduced as well. Differential expressions of proteins such as p53, Bax, caspase-3, and caspase-9 were significantly up-regulated in PFOS-exposed hosts, whereas Bcl-2 expression was significantly down-regulated. One possible mechanism for the findings here was that PFOS could overwhelm homeostasis of anti-oxidative systems, boost ROS generation, impact on mitochondria, and affect protein expression of apoptotic regulators, the latter of which resulted in initiation of the apoptosis program. Results from this study may provide a new insight into the potential adverse effects of PFOS exposure on humans, at the cellular level.